(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: Evaluate the safety, effectiveness, and clinical outcomes of patients treated with smallincision surgical removal of corneal tissue (ReLEx SMILE) using a flap thickness of 100μ compared to 160μ. Method: A non-randomized clinical trial with a prospective control group was conducted on 100 eyes of 50 patients undergoing myopia treatment ranging from -1D to -6D spherical equivalent using ReLEx SMILE. Among them, 25 patients were treated with a standard flap thickness of 100μ, while the remaining 25 patients were treated with a flap thickness of 160μ in both eyes. Parameters including corneal refractive power, uncorrected visual acuity, corrected visual acuity (logMAR), corneal astigmatism, higher-order aberrations, and dry eye were assessed, along with subjective questionnaires at 2 weeks and 3 months post-surgery. The average follow-up time was 90 ± 15 days. Results: At 2 weeks and 3 months post-surgery, compared to preoperative measurements, the mean values of uncorrected and corrected distance visual acuity, corneal astigmatism, contrast sensitivity, and higher-order aberrations showed no statistically significant differences (p > 0.05) between the two study groups. However, Schirmer’s II and tear breakup time (TBUT) at 3 months were significantly reduced in the group treated with the 100μ flap thickness, but not in the 160μ group. Patients in both groups reported minimal subjective complaints in response to questionnaires. Conclusion: ReLEx SMILE with a flap thickness of 160μ demonstrates comparable safety and effectiveness to the 100μ flap thickness, without any statistically significant complications observed when using a thicker flap. Additionally, postoperative dry eye symptoms were significantly reduced in the 160μ group, offering an advantage in treating patients with pre-existing dry eye or contact lens wearers.